Implementation of Sustainability Standard into Commodity Supply Chain Networks: A Processual Case Approach - Sidikat, Shitu; Rohaya, Mohd Nor (Human Resource Management Academic Research Society, 2017)
This paper investigates the process of implementing sustainability standard into shea butter supply chain networks. Using an exploratory processual case study methodology informed by Pettigrew Contextual Approach. In this paper a conceptual model was developed using the relationship among the external actors to investigate the contextual factors that support or obstruct the implementation process over a period of time. The findings suggest that the standard setting organizations are the pace-setters for the other external actors in the implementation process, while contextual factors related to socio-cultural context, historical context and political context are responsible for the slow implementation process in the supply chain networks. Research implication for the study was presented together with contributions and conclusion.